The process of decentralization to 5 years Bicentennial ¿What are the challenges we face in the future? - Vidal Coronado, Raúl Martín (2021)
This article is to evaluate cursory way, what is the state of the decentralization process in our country and what should be the intervention of administrative law to facilitate the modernization of the State and the satisfaction of the interests of the governed.